Cobalt/polypyrrole nanocomposites with controllable electromagnetic properties1. Issue 16 (28th April 2015) - Wang, Haicheng; Ma, Ning; Yan, Zhiran; Deng, Ling; He, Jun; Hou, Yanglong; Jiang, Yong; Yu, Guanghua
<x xml:space="preserve">Abstract</x> Cobalt/polypyrrole nanocomposites for electromagnetic wave absorbents were prepared by in situ polymerization of pyrrole in the presence of Co nanoparticles. With different ratios of Co/polypyrrole, these nanocomposite materials can show controllable electromagnetic properties.